Photovoltaic module packaging assembly without main grid battery

By adopting a composite packaging film with a double-layer structure in the packaging film of the main gate photovoltaic module, the problems of insufficient conductive connection of the welding tape and oxidation and corrosion of the metal materials are solved, and the components are high reliability and power improvement are achieved.

CN223007821UActive Publication Date: 2025-06-20GUANGZHOU HEIBEN NEW MATERIAL TECH CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202421773657.7
Authority / Receiving Office
CN · China
Patent Type
Utility models(China)
Current Assignee / Owner
Filing Date
2024-07-24
Publication Date
2025-06-20
Estimated Expiration
2034-07-24

AI Technical Summary

Technical Problem

During the packaging process of the main gate photovoltaic module, the welding tape is wrapped in a film, resulting in insufficient conductive connection, and the active metal material is prone to oxidation and corrosion, affecting the reliability and power of the component.

Method used

A composite encapsulation film with a double-layer structure includes a thermoset bonding layer and a thermoplastic corrosion inhibitor layer. The thermoset bonding layer is used to contact with glass or back panel to provide strong bonding force; the thermoplastic corrosion inhibitor is used to contact with the battery cell, ensuring priority metallization of the welding tape and the battery cell, and contains a corrosion inhibitor to prevent oxidative corrosion of the metal material.

Benefits of technology

It effectively solves the problem of shadows under the welding tape, ensures good connection between the welding tape and the battery cell, improves the long-term reliability and power performance of the components, and reduces production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN223007821U_ABST
    Figure CN223007821U_ABST
Patent Text Reader

Abstract

The utility model discloses a photovoltaic module packaging assembly of a main-grid-free battery, a laminated structure of the photovoltaic module packaging assembly sequentially comprises photovoltaic front plate glass, a first metal corrosion inhibition packaging adhesive film, a main-grid-free battery string, a second metal corrosion inhibition packaging adhesive film and a photovoltaic back plate, and each metal corrosion inhibition packaging adhesive film is a composite packaging adhesive film with a double-layer structure. Comprising a thermocuring bonding layer and a thermoplastic corrosion inhibition layer, the thermocuring bonding layer of a first metal corrosion inhibition packaging adhesive film is in contact with photovoltaic front plate glass, and the thermocuring bonding layer of a second metal corrosion inhibition packaging adhesive film is in contact with a photovoltaic back plate. During packaging, the contact glass is a thermocuring bonding layer of the metal corrosion inhibition packaging adhesive film, so that a long-term and effective thermocuring bonding force is provided; the contact battery piece is the thermoplastic corrosion inhibition layer of the metal corrosion inhibition packaging adhesive film, the fluidity of thermoplastic materials is small, it can be guaranteed that the welding strip and the battery piece are metalized preferentially, the problem that shadows exist under the welding strip during main-grid-free assembly packaging EL detection can be effectively solved, and the long-term reliability of a photovoltaic assembly is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The utility model belongs to the technical field of photovoltaic encapsulation films, and particularly relates to a photovoltaic module encapsulation assembly for a non-main-grid battery. Background Art

[0002] With the development of technology, the main-grid technology of solar cells has evolved from MBB and SMBB to 0BB (non-main-grid). The non-main-grid technology is a further upgrade of the SMBB technology, with obvious cost reduction advantages. The non-main-grid technology directly eliminates the main grid of the battery cell, and prepares the fine grid of the battery through silver-coated copper paste or uses electroplated copper technology to prepare the grid line, further reducing silver consumption; in addition, in the module link, an embedded circular copper solder tape is used to replace the function of the silver main grid of the battery to conduct current. The commonly used solder tape diameter of MBB modules is 0.2 - 0.4 mm, while the 0BB solder tape diameter only needs 0.2 mm, with a smaller shading area and the ability to improve the module power. Currently, the non-main-grid technology is widely used in IBC, HJT, TOPCON and other batteries.

[0003] Problems in the materials of the non-main-grid technology: The fine grid of the non-main-grid technology uses low-cost silver-coated copper paste or electroplated pure copper to replace the traditional pure silver fine grid, and the pure silver main grid of the battery is also replaced by an embedded circular copper solder tape. The chemical property of copper material is more active than silver, and it is easy to oxidize and corrode, resulting in a decrease in electrical conductivity, which poses higher requirements for the encapsulation material. Patent CN 117701189 A uses magnesium oxide as an acid-absorbing material to adsorb acetic acid and water vapor of EVA, improving the problems of solder tape corrosion of the battery cell, blackening of the battery cell and delamination of the film, but the acetic acid generated during the aging process of the EVA material inevitably corrodes the battery material.

[0004] Problems in the process of the non-main-grid technology: In the non-main-grid mass production process, first apply a glue dot body (adhesives such as UV glue, hot melt glue, etc.) to cure the whole solder tape on the battery cell by using equipment such as UV lamps and ovens, and then realize the alloying of the solder tape and the battery cell through lamination. The difference between this scheme and the welding and dispensing scheme is that welding is not required, and it can be fixed by dispensing or screen printing, with strong stability. However, currently, the conventional EVA and POE films used in the industry have a low melting temperature and large fluidity. When the module is encapsulated, the film material melts prior to the solder tape, resulting in the problem of shadows under the solder tape during EL detection (the solder tape is wrapped by EVA and POE materials, and the solder tape cannot form an electrical connection with the battery cell). To solve this problem, the industry uses electron radiation to pre-crosslink the EVA and POE films to reduce the fluidity of the films to solve the shadows under the solder tape during encapsulation EL detection. However, the pre-crosslinked film results in insufficient bonding force between the solder tape and the battery cell, poor module reliability, and complex and costly processes. In addition, the non-main-grid photovoltaic industry uses a low-fluidity thermoplastic PVB film to solve the EL shadow problem, but the pure PVB film has a high price, which is not conducive to cost reduction, efficiency improvement and application promotion of the module. Content of the Utility Model

[0005] The purpose of the present utility model is to provide a photovoltaic module encapsulation component for a main-gridless battery with improved performance and low cost.

[0006] A photovoltaic module encapsulation component for a main-gridless battery, whose laminated structure sequentially includes a photovoltaic front plate glass, a first metal corrosion-inhibiting encapsulation film, a main-gridless battery string, a second metal corrosion-inhibiting encapsulation film, and a photovoltaic backplane. Each metal corrosion-inhibiting encapsulation film is a composite encapsulation film with a double-layer structure, including a thermosetting adhesive layer and a thermoplastic corrosion-inhibiting layer. The thermosetting adhesive layer of the first metal corrosion-inhibiting encapsulation film contacts the photovoltaic front plate glass, and the thermoplastic corrosion-inhibiting layer of the first metal corrosion-inhibiting encapsulation film contacts the main-gridless battery string. The thermosetting adhesive layer of the second metal corrosion-inhibiting encapsulation film contacts the photovoltaic backplane, and the thermoplastic corrosion-inhibiting layer of the second metal corrosion-inhibiting encapsulation film contacts the main-gridless battery string..

[0007] Further, the thickness of the thermosetting adhesive layer is 0.30 - 0.60 mm.

[0008] Further, the thickness of the thermoplastic corrosion-inhibiting layer is 10 - 200 μm.

[0009] Compared with the prior art, the photovoltaic module encapsulation component of the present utility model adopts a metal corrosion-inhibiting encapsulation film. The metal corrosion-inhibiting encapsulation film is a composite encapsulation film with a double-layer structure, including a thermosetting adhesive layer and a thermoplastic corrosion-inhibiting layer. When the component is encapsulated, the layer contacting the glass (or backplane) is the thermosetting adhesive layer of the film, providing a long-term and effective thermosetting adhesive force; while the layer contacting the battery chip is the thermoplastic corrosion-inhibiting layer of the film. The high-molecular-weight thermoplastic material has low fluidity, which can ensure preferential metallization (the connection between the solder strip and the battery is conductive) during the lamination process of the solder strip and the battery chip, and can effectively solve the problem of shadows under the solder strip during the EL detection of the main-gridless component encapsulation. Moreover, the corrosion inhibitor contained in the material can form a protective layer with the metal grid lines, solder strips, conductive coatings, and bus bar materials on the battery surface, effectively preventing the oxidation and corrosion of active metal materials and improving the long-term reliability of the photovoltaic module. Description of the Drawings

[0010] Figure 1 It is a schematic diagram of a metal corrosion-inhibiting encapsulation film of the present utility model Figure two

[0011] Figure 2 It is a schematic diagram of the encapsulation of a photovoltaic module for a main-gridless battery of the present utility model. Detailed Embodiments

[0012] Please refer to Figure 1 - Figure 2, a photovoltaic module encapsulation component of a main-gridless battery of the present utility model, its laminated structure sequentially includes a photovoltaic front plate glass 3, a first metal corrosion-inhibiting encapsulation film, a main-gridless battery string 4, a second metal corrosion-inhibiting encapsulation film, and a photovoltaic back plate 5. Each metal corrosion-inhibiting encapsulation film is a composite encapsulation film with a double-layer structure, including a thermosetting adhesive layer 11 and a thermoplastic corrosion-inhibiting layer 12. The thermosetting adhesive layer 11 of the first metal corrosion-inhibiting encapsulation film contacts the photovoltaic front plate glass 3, and the thermosetting adhesive layer 11 of the second metal corrosion-inhibiting encapsulation film contacts the photovoltaic back plate 5.

[0013] Further, the thickness of the thermosetting adhesive layer 11 is 0.30 - 0.60 mm; the thickness of the thermoplastic corrosion-inhibiting layer 12 is 10 - 200 μm.

[0014] Specifically, the metal corrosion-inhibiting encapsulation film has a two-layer structure, which is sequentially a thermosetting adhesive layer and a thermoplastic corrosion-inhibiting layer. The thermosetting adhesive layer is melt-extruded by a single-screw extruder according to the formula to obtain a base film with a thickness of 0.3 - 0.6 mm; then, the corrosion-inhibiting layer glue is prepared according to the formula, and the glue is coated on any surface of the base film through a slot coating process, and the solvent is removed by a drying oven to form a thermoplastic corrosion-inhibiting layer with a structural thickness of 10 - 200 μm on the base film, and finally a metal corrosion-inhibiting encapsulation film with a double-layer structure is obtained. A metal corrosion-inhibiting encapsulation film of the present utility model is applied to the encapsulation of a photovoltaic module of a main-gridless battery. The surface of the metal corrosion-inhibiting encapsulation film contacting the photovoltaic glass (or back plate) is the thermosetting adhesive layer, and the surface of the metal corrosion-inhibiting encapsulation film contacting the battery cell is the thermoplastic corrosion-inhibiting layer. The structure of the photovoltaic module encapsulation component is a photovoltaic front plate glass, a metal corrosion-inhibiting encapsulation film, a main-gridless battery string, a metal corrosion-inhibiting encapsulation film, and a photovoltaic back plate.

[0015] The following further describes the present utility model in conjunction with specific embodiments.

[0016] In the present utility model, unless otherwise specified, all devices and raw materials can be purchased from the market or are commonly used in this industry. The methods in the following embodiments, unless otherwise specified, are conventional methods in this field.

[0017] In the present utility model, it should be particularly noted that for the corrosion inhibitor in the thermoplastic corrosion-inhibiting layer and its preparation method, the corrosion inhibitor is one or more of benzotriazole derivatives, and its structural formula is:

[0018]

[0019] In formulas [A] and [B], R1, R2, and R3 are H, alkyl, aryl, or heterocyclic groups.

[0020] (1) When R1, R2, and R3 in formula [A] are all H, the method of patent CN201510774530.6 can be adopted to obtain a corrosion inhibitor with the following structural formula [A-1]:

[0021]

[0022] (2) When in formula [B], R2 and R3 are aryl groups with the same structure and R1 is an alkyl group; the method of Patent CN 103562323B can be adopted to obtain the corrosion inhibitor with the following structure of structural formula [B-1]:

[0023]

[0024] (3) When in formula [A], R2 and R3 are aryl groups with the same structure and R1 is an alkyl group; the corrosion inhibitor with the following structure of structure [A-2] is obtained:

[0025]

[0026] Preparation method of [A-2]: A mixture of 4,7-dibromo-1H-2-isobutylbenzotriazole (1.32 g, 4.0 mmol), 4-tert-butylphenylboronic acid (10.0 mmol), tetrakis(triphenylphosphine)palladium(0) (1.00 g, 0.86 mmol), an aqueous solution of sodium carbonate (2.12 g, 20 mmol) in water (15 mL), butanol (50 mL) and toluene (30 mL) was vigorously stirred and heated at 100 °C under argon for 16 hours. The reaction mixture was poured into water (300 mL), stirred for 30 minutes and extracted with toluene / ethyl acetate / hexane (5∶3∶2, 500 mL). The volatiles were removed under reduced pressure and the residue was chromatographed (silica gel, hexane / dichloromethane, 1∶1). The separated product was recrystallized from ethanol to obtain [A-2] as 4,7-bis(4-tert-butylphenyl)-2-isobutyl-1H-benzotriazole.

[0027]

[0028] (4) When in formula [A], R2 and R3 are aryl groups with the same structure and R1 is an alkyl group; the corrosion inhibitor with the following structure of structure [A-3] is obtained:

[0029]

[0030] Preparation method of [A-3]: A mixture of 4,7-dibromo-1H-2-isobutylbenzotriazole (1.32 g, 4.0 mmol), phenylboronic acid (10.0 mmol), tetrakis(triphenylphosphine)palladium(0) (1.00 g, 0.86 mmol), an aqueous (15 mL) solution of sodium carbonate (2.12 g, 20 mmol), butanol (50 mL), and toluene (30 mL) was vigorously stirred and heated at 100 °C under argon for 16 h. The reaction mixture was poured into water (300 mL), stirred for 30 min, and extracted with toluene / ethyl acetate / hexane (5:3:2, 500 mL). Volatiles were removed under reduced pressure, and the residue was chromatographed (silica gel, hexane / dichloromethane, 1:1). The separated product was recrystallized from ethanol to obtain [A-3] as 4,7-bis(phenyl)-2-isobutyl-1H-benzotriazole.

[0031]

[0032] In the present utility model, it is necessary to specifically describe the preparation method of the corrosion-inhibiting layer glue:

[0033] By weight, 100 parts of a thermoplastic matrix resin, 1 - 20 parts of a plasticizer, 0.1 - 1 part of a coupling agent, and 0.5 - 10 parts of a corrosion inhibitor are placed in a stirring kettle, and then 100 - 1000 parts of a solvent are added to the stirring kettle and stirred until dissolved to obtain the corrosion-inhibiting layer glue.

[0034] Case 1: 100 parts of a PVB thermoplastic matrix resin (Kuraray / B16H), 5 parts of a plasticizer (3GO, full name triethylene glycol diisooctanoate, Shandong Kexing Chemical Co., Ltd.), 0.1 part of a coupling agent (3-glycidyletheroxypropyltrimethoxysilane), and 3 parts of a corrosion inhibitor of formula [A-1] (benzotriazole) by weight are placed in a stirring kettle, and then 500 parts of ethanol are added to the stirring kettle and stirred at room temperature for 6 h until completely dissolved to obtain the corrosion-inhibiting layer glue.

[0035] Case 2: 100 parts of a TPU thermoplastic matrix resin (Wanhua Chemical / WHT-A190), 3 parts of a plasticizer (DOA, full name dioctyl adipate, Shandong Kexing Chemical Co., Ltd.), 0.5 part of a coupling agent (γ-aminopropyltriethoxysilane), and 10 parts of a corrosion inhibitor of formula [A-1] (benzotriazole) by weight are placed in a stirring kettle, and then 500 parts of dichloromethane are added to the stirring kettle and stirred at room temperature for 7 h until completely dissolved to obtain the corrosion-inhibiting layer glue.

[0036] Case 3: 100 parts by weight of epoxy thermoplastic matrix resin (Japan Daicel / EHPE3150), 15 parts of plasticizer (DOP, full name dioctyl phthalate, Shandong Kexing Chemical Co., Ltd.), 0.5 parts of coupling agent (3-glycidyloxypropyltrimethoxysilane), and 0.5 parts of corrosion inhibitor of formula [A-3] (4,7-bis(phenyl)-2-isobutyl-1H-benzotriazole) are placed in a stirring tank, and then 300 parts of acetone are added to the stirring tank, and stirred at room temperature for 4 hours to completely dissolve to obtain a corrosion inhibition layer glue.

[0037] Case 4: 100 parts by weight of PVB thermoplastic matrix resin (Kuraray / B60T), 20 parts of hydrogenated DOTP plasticizer (Hanwha Chemical environmentally friendly plasticizer / ECO-DEHCH), 0.5 parts of coupling agent (γ-aminopropyltriethoxysilane), and 7 parts of a mixed corrosion inhibitor of formula [A-2] / formula [B-1]=1 are placed in a stirring tank, and then 800 parts of isopropanol are added to the stirring tank, and stirred at room temperature for 8 hours to completely dissolve to obtain a corrosion inhibition layer glue.

[0038] Case 5: 100 parts by weight of PVA thermoplastic matrix resin (Kuraray / PVA103), 1 part of a mixed plasticizer of hydrogenated DOTP / DBS = 1:1 (hydrogenated DOTP is Hanwha Chemical's environmentally friendly plasticizer / ECO-DEHCH, DBS is dibutyl sebacate produced by Shandong Kexing Chemical Co., Ltd.), 1 part of a coupling agent (γ-aminopropyltriethoxysilane), and 0.5 parts of a corrosion inhibitor of formula [A-2] are placed in a stirring tank, and then 1000 parts of an ethanol aqueous solution (water: ethanol = 1:1) are added to the stirring tank, heated and stirred at 90 degrees for 5 hours to completely dissolve, and a corrosion inhibition layer glue is obtained.

[0039] Case 6: 100 parts by weight of TPU thermoplastic emulsion (McGlenn / HydrosizeTM U6-01), 3 parts of DOA plasticizer (DOA, full name dioctyl adipate, Shandong Kexing Chemical Co., Ltd.), 0.5 parts of coupling agent (γ-aminopropyltriethoxysilane), and 0.5 parts of corrosion inhibitor of formula [A-3] were placed in a stirring tank, and then 100 parts of pure water were added to the stirring tank, and stirred at room temperature for 1 hour to obtain a corrosion inhibition layer glue.

[0040] Case 7: 100 parts by weight of PI thermoplastic emulsion (McGlenn / HydrosizeTM HP-1632), 3 parts of DOA plasticizer (DOA, full name dioctyl adipate, Shandong Kexing Chemical Co., Ltd.), 0.5 parts of coupling agent (γ-aminopropyltriethoxysilane), and 0.5 parts of corrosion inhibitor of formula [A-3] were placed in a stirring tank, and then 100 parts of pure water were added to the stirring tank, and stirred at room temperature for 1 hour to obtain a corrosion inhibition layer glue.

[0041] Comparative Example 1: Put 100 parts by weight of PVB thermoplastic matrix resin (Kuraray / B60T), 5 parts of 3GO plasticizer (3GO, full name triethylene glycol diisooctanoate, Shandong Kexing Chemical Co., Ltd.), 0.1 part of coupling agent (3-glycidyletheroxypropyltrimethoxysilane), and 0 part of corrosion inhibitor into a stirring kettle. Then add 800 parts of isopropanol to the stirring kettle and stir at room temperature for 8 hours until completely dissolved to obtain the corrosion-inhibiting layer glue.

[0042] Comparative Example 2: Put 100 parts by weight of PVB thermoplastic matrix resin (Kuraray / B60T), 5 parts of 3GO plasticizer (3GO, full name triethylene glycol diisooctanoate, Shandong Kexing Chemical Co., Ltd.), 0.1 part of coupling agent (3-glycidyletheroxypropyltrimethoxysilane), and 0 part of corrosion inhibitor into a stirring kettle. Then add 800 parts of isopropanol to the stirring kettle and stir at room temperature for 8 hours until completely dissolved to obtain the corrosion-inhibiting layer glue.

[0043] Comparative Example 3: Put 100 parts by weight of TPU thermoplastic matrix resin (Wanhua Chemical / WHT-A190), 3 parts of plasticizer (DOA, full name dioctyl adipate, Shandong Kexing Chemical Co., Ltd.), 0.5 part of coupling agent (γ-aminopropyltriethoxysilane), and 0 part of corrosion inhibitor into a stirring kettle. Then add 500 parts of dichloromethane to the stirring kettle and stir at room temperature for 7 hours until completely dissolved to obtain the corrosion-inhibiting layer glue.

[0044] In the present utility model, it should be particularly noted that the metal corrosion-inhibiting encapsulation adhesive film is applied to a lamination method for encapsulating a main-gridless battery photovoltaic module: Component laying sequence: photovoltaic front panel glass, metal corrosion-inhibiting encapsulation adhesive film, main-gridless battery string (fixed by UV dispensing), metal corrosion-inhibiting encapsulation adhesive film, photovoltaic backplane. Among them, the surface of the metal corrosion-inhibiting encapsulation adhesive film in contact with the photovoltaic glass (or backplane) is the bonding layer, and the surface of the metal corrosion-inhibiting encapsulation adhesive film in contact with the battery cell is the thermoplastic corrosion-inhibiting layer.

[0045] Component lamination process: After laying the adhesive films and batteries in the examples and comparative examples, heat and laminate them to make the samples to be tested. Among them, the lamination process parameters are a temperature of 145 °C, air extraction for 6 min, pressurization for 1 min, and pressure holding for 12 min. PID and EL appearance tests: Refer to the standards IEC61215 and IECIEC62804 for testing. The experimental and test results of the examples and comparative examples are as described in Table 1.

[0046] Table 1 lists the technical solutions described in Example 17 and Comparative Examples 1-3

[0047]

[0048]

[0049]

[0050] As can be seen from Table 1 and Comparative Example 4, the pure EVA encapsulation film is not friendly to the main-gridless cell module. Due to the low melting point and high fluidity of the EVA material, when used for the encapsulation of main-gridless UV dispensing cells, the EVA film material melts prior to the solder tape during module lamination. After lamination, the EVA resin fills the space between the solder tape and the cell, and the solder tape cannot form an electrical connection with the cell. When the module is detected by EL using the IEC61215 standard, it is found that there is a shadow problem under the solder tape. Moreover, after testing by the IEC62804 standard PID288, it is found that the busbars, solder tapes, and fine grids are severely corroded, and the module power has decreased by 25.1%.

[0051] As can be seen from Table 1 and Comparative Examples 1-3, a layer of thermoplastic TPU and PVB is coated on the base film of the EVA adhesive layer. After module lamination, when the module is detected by EL using the IEC61215 standard, it is found that the problem of shadow under the solder tape is solved. It shows that treating a layer of thermoplastic PVB and TPU materials on the EVA base film can effectively solve the EL shadow problem. However, no metal corrosion inhibitor component is added to the thermoplastic layer of Comparative Examples 1-3. After the module is tested by the IEC62804 standard PID288, it is found that the solder tapes and fine grids are severely corroded, and the module power has decreased by 10-18%. The problem of corrosion of the fine grids and solder tape metal materials on the surface of the main-gridless cell cannot be solved. However, compared with Comparative Example 4, the busbars are not corroded, which is an improvement over the pure EVA film.

[0052] As can be seen from Table 1, for Examples 1-7 and Comparative Examples 1-3, a layer of thermoplastic material is coated on the base film of the thermosetting adhesive layer. After module lamination, when the module is detected by EL using the IEC61215 standard, it is found that the problem of shadow under the solder tape is solved. As can be seen from Table 1, in Examples 3 and 5, 0.5 part of metal corrosion inhibitor component is added to the thermoplastic layer. After the module is tested by the IEC62804 standard PID288, it is found that the fine grids are slightly corroded, and the module powers have decreased by 5.4% and 7.2% respectively. Compared with Comparative Examples 1-3, the problem of corrosion of the fine grids and solder tape metal materials on the surface of the main-gridless cell is effectively solved.

[0053] As can be seen from Table 1, the thermoplastic glue coating materials of Examples 1, 2, 4, 6, and 7 contain 1.5 to 10 parts of corrosion inhibitor. After the module is tested by the IEC62804 standard PID288, no corrosion of the solder tapes and fine grids on the cell surface is found, and the module power has decreased by 2%-3%. Comparing Example 4 with Example 2, in Example 4, two kinds of corrosion inhibitors are compounded, and the metal corrosion inhibition effect is better. It is reflected in that after the module is tested by the IEC62804 standard PID288, the power decrease of Example 4 is less than 1%, and the test value only decreases by 0.5%.

Claims

1. A photovoltaic module packaging assembly without a main grid cell, characterized in that: Its stacked structure includes photovoltaic front panel glass, a first metal corrosion-inhibiting packaging film, a main-grid-free battery string, a second metal corrosion-inhibiting packaging film and a photovoltaic back panel in sequence. Each metal corrosion-inhibiting packaging film is a composite packaging film with a double-layer structure, including a thermosetting adhesive layer and a thermoplastic corrosion-inhibiting layer. The thermosetting adhesive layer of the first metal corrosion-inhibiting packaging film contacts the photovoltaic front panel glass, the thermoplastic corrosion-inhibiting layer of the first metal corrosion-inhibiting packaging film contacts the main-grid-free battery string, the thermosetting adhesive layer of the second metal corrosion-inhibiting packaging film contacts the photovoltaic back panel, and the thermoplastic corrosion-inhibiting layer of the second metal corrosion-inhibiting packaging film contacts the main-grid-free battery string.

2. The photovoltaic module packaging assembly without a main grid cell according to claim 1, characterized in that: The thickness of the thermal curing adhesive layer is 0.30-0.60 mm.

3. The photovoltaic module packaging assembly without a main grid cell according to claim 1, characterized in that: The thickness of the thermoplastic corrosion inhibition layer is 10-200 μm.

Citation Information

Patent Citations

  • Highly fluorescent and photostable chromophores for improving sunlight collection efficiency

    CN103562323B

  • Synthesis method of benzotriazole

    CN105237488A

  • Low-gram-weight adhesive film for main-grid-free photovoltaic module and preparation method of low-gram-weight adhesive film

    CN117701189A

  • Shiftable table of hydraulic forming machine

    CN2440618Y